2022
DOI: 10.1177/09612033221115628
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of thiol/disulfide hemostasis and serum Ischemia modified albumin as oxidative stress biomarkers in systemic lupus erythematosus patients: Relationship with major organ involvement and disease activity

Abstract: Objectives We aimed to compare thiol/disulfide hemostasis and serum ischemia-modified albumin (IMA) levels, which are indicators of oxidative stress (OS), in patients with systemic lupus erythematosus (SLE), with the healthy control (HC) group and to evaluate the relationship of these parameters with disease activity and major organ involvement. Material-Methods Eighty-four SLE patients and 96 HCs were included in this study. The disease activity of SLE patients was calculated using The Systemic Lupus Erythema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 45 publications
(71 reference statements)
1
0
0
Order By: Relevance
“…While some studies have demonstrated an increase in IMA levels in rheumatic diseases, there are also studies with conflicting results. Ermurat et al [28] reported no difference in IMA levels between SLE patients and HCs in their study.…”
Section: Discussionmentioning
confidence: 65%
“…While some studies have demonstrated an increase in IMA levels in rheumatic diseases, there are also studies with conflicting results. Ermurat et al [28] reported no difference in IMA levels between SLE patients and HCs in their study.…”
Section: Discussionmentioning
confidence: 65%
“…After reviewing the full text of the remaining 22 articles, a further two were excluded because of missing data (one study) and no case‐control design (one study). Therefore, 20 studies were selected for analysis 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 (Table 1 ). The risk of bias was low in 18 studies, 70 , 71 , 72 , 73 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 moderate in one, 75 and high in the remaining one 74 (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, 20 studies were selected for analysis 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 (Table 1 ). The risk of bias was low in 18 studies, 70 , 71 , 72 , 73 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 moderate in one, 75 and high in the remaining one 74 (Table 2 ). The cross‐sectional nature of the selected studies primarily accounted for the low initial certainty of evidence (level 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations